Győrgy Targonski’s life and work - Choczewski, Bogdan; Targonski, Jolán (Annales Mathematicae Silesianae, 1999)
The paper is based on the Curriculum Vitae of Győrgy Targoński (March 27. 1928 - January 10. 1998) written by the second author, and is completed by a survey of his domains of research with special attention to selected papers. Professor Targonski's scientific legacy consists of over hundred research papers, books, lecture notes and reports, contributions to meetings (problems, remarks, abstracts of lectures) and of proceedings of the ECIT. These are all documented in the three lists attached to the article.